Association of Neighborhood Food Environment and Physical Activity Environment With Obesity: A Large-Scale Cross-Sectional Study of Fifth- to Ninth-Grade Children in Japan. (1st November 2021) - Oishi, Kan; Aoki, Takumi; Harada, Tetsuo; Tanaka, Chiaki; Tanaka, Shigeho; Tanaka, Hideki; Fukuda, Kazuhiko; Kamikawa, Yasuko; Tsuji, Nobuhiro; Komura, Keisuke; Kokudo, Shohei; Morita, Noriteru; et al.
Objective: This study examined the relationship between neighborhood food and physical activity environment, and obesity among elementary and junior high school students in Japan.Methods: The participants were fifth- to ninth-grade children (n=7277), who were attending municipal schools in Japan. Percent overweight (POW) was calculated using their age, gender, height, and weight, which were collected through a questionnaire. A POW of < 20% was considered non-obese, while ≥ 20% was considered obese. Furthermore, using a geographic information system, we investigated the density of convenience stores, fast-food stores, casual restaurants, supermarkets and department stores, parks, sports facilities, stations, and intersections in the school district. Additionally, from the census, we obtained information regarding the population density of the municipality where the participants' schools were located. Multiple logistic regression analysis was used to examine the relationship between obesity and food environment (the food environment model), between obesity and physical activity environment (the physical activity environment model), and among obesity, food, and physical activity environment (the food and physical activity environment model).Results: In the food environment model and the food and physical activity environment model, the density of convenience stores showed a significant positive association. In the physical activity environment model, the density of stations showed a significant negative association.Conclusion: This study's findings can contribute to the development of appropriate community interventions for improving children's health in Japan and similar areas.